Analysis of Household Financial Management for Work from Home Affected Employees (Case Study on Employees of Insurance Industry Companies in Surabaya) - Muttaqiin, Ninnasi (Universitas Nahdlatul Ulama Surabaya, 2020)
This study was conducted to examine the effect of work from home policy caused by coronavirus epidemic on household financial management of insurance industry employees in Surabaya. This study uses a qualitative method by conducting interviews. The variables used are household consumption, household savings, household investment, household insurance, and retirement planning. The sample selection using purposive sampling method, obtained seven sources who then provide answers to questions during in-depth interviews. The results showed that the work from home policy had a very significant effect on the condition of household financial management in the variables of household consumption, household savings, and household investment. On the other hand, work from home policy does not really affect household insurance management and retirement planning for employees of the insurance industry in Surabaya.